WILL ONE-YEAR-OLD IBRAHIMJAN BE FATHERLESS!? - Karimov F. M.; Karimova G. M. (Journals Park Publishing, 2023)
The article states that the family, which is considered the main core of any society, is sacred, it is necessary to explain the importance of the family to citizens, it is necessary to strengthen spiritual and moral education in order to prevent divorces caused by betrayal of the family.
Keywords: constitution, family, society, judgment, family betrayal, nation, spirituality, family life, moral education.